Enhanced production of bioactive compounds from marine microalgae Tetraselmis tetrathele under salinity and light stresses: A two-stage cultivation strategy. (May 2023) - Nezafatian, Elham; Farhadian, Omidvar; Yegdaneh, Afsaneh; Safavi, Maliheh; Daneshvar, Ehsan; Bhatnagar, Amit
Graphical abstract: Highlights: Two-stage cultivation of Tetraselmis tetrathele was conducted in food wastewater . Abiotic stresses were applied during stationary growth phase. Salinity stress could enhance pigment contents of Tetraselmis tetrathele . Salinity and light intensity stresses increased antioxidant capacity of microalgae. Abstract: This study leveraged the salinity and light intensity stresses during the stationary phase for enhancing the pigment contents and antioxidant capacity of Tetraselmis tetrathele . The highest pigments content was obtained in cultures under salinity stress (40 g L −1 ) illuminated using fluorescent light. Furthermore, the best inhibitory concentration (IC50 ) for scavenging the 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals was found as 79.53 µg mL −1 in ethanol extract and cultures under red LED light stress (300 µmol m −2 s −1 ). The highest antioxidant capacity in a ferric-reducing antioxidant power (FRAP) assay (1, 778.6 µM Fe +2 ) was found in ethanol extract and cultures under salinity stress illuminated using fluorescent light. Maximum scavenging of the 2.2-diphenyl-1-picrylhydrazyl (DPPH) radical was found in ethyl acetate extracts under light and salinity stresses. These results indicated that abiotic stresses could enhance the pigment and antioxidant components of T. tetrathele, which are value-added compounds in the pharmaceutical, cosmetic, and food industries.